Analgesic and Antidiarrheal Properties of the Latex of Calotropis Procera - Das, Amitav (International Journal of Pharmaceutical & Biological Archive, 2011)
Calotropis procera (Ait.) R. Br. (Asclepiadaceae) is a Bangladeshi medicinal plant used traditionally to treat a various diseases. Phytochemical analyses as well as antidiarrheal and analgesic potentials of C. procera were evaluated. The ethanol extracts of the latex of the plant was used in this study. The analgesic activity was carried out against acetic acid-induced writhing test. The antidiarrheal potential was studied in castor oil induced diarrhea in mice. Mayer and Dragendroff’s reagents, Mg and HCl, 1% gelatin-10% NaCl solution, Benedict’s and Fehling’s reagents were used for the analysis of alkaloids, flavonoids, tannin and reducing sugar respectively. Results showed that the intraperitoneal administration of ethanol extracts at 250 and 500 mg/kg produced a significant (p <0.05) and dose dependent analgesic effect against acetic acid induced writings. On the other hand, in castor oil induced diarrhea, oral administration at same doses was less pronounced as compared to a 4 mg/kg oral dose of loperamide. Furthermore, our phytochemical analysis also revealed the presence of alkaloids and tannins. This evidence clearly indicates that the ethanol extracts of Calotropis Procera possess strong analgesic potential coupled with antidiarrheal efficacy which may explain the use of the plant in traditional medicine as a popular antidiarrheal and analgesic recipe.